HUBUNGAN PERILAKU PASIEN TERHADAP KEPATUHAN MEMBAWA KARTU IDENTITAS BEROBAT DI RS KHUSUS MATA MEDAN BARU TAHUN 2022 - Meliala, Sri Agustina Meliala; Fitria, Dilla (Jurnal Infokes, 2023)
Human conduct is divided into three domains: knowledge, attitudes, and acts. Compliance is a type of behavior that results from interactions between health professionals and patients. When the patient’s conduct is needed to comply with carrying a Medical Identity Card (MIC) when registering at the registration unit, patients carrying a MIC make it simpler for registration officers to find the patient’s identification. Based on the findings of an initial survey of 10 outpatients conducted through interviews, patients were not yet compliant in carrying a MIC, because they did not understand the benefits and purpose of carrying a MIC while seeking treatment at health centre. The study aimed to examine the association between patient behavior and adherence to carrying MNH at Medan Baru Eye Center in 2022. The study employed was quantitative using a cross-sectional approach, and conducted at Medan Baru Eye Center, located in Abdullah Lubis District. The population was 3881 patients who had gotten treatment in the previous year at Medan Baru Eye Center. The sample was done by chance. The research instrument was a questionnaire that has been validated and reliable. Finally, with a p value of 0.05, knowledge, attitude, and action factors associated with adherence to carrying identity cards for treatment. The Medan Baru Eye Center were advised to educate the population about the need of having a Medical Identity Card (MIC) while seeking treatment at further time. Keywords: Behavior, Compliance, Medical Identity Card (KIB)